Skrining Fitokimia dan Toksisitas dari Ekstrak Daun Pecut Kuda (Stachytarpheta jamaicenesis (L.) Vahl) - Irawan Wijaya Kusuma; Erwin Erwin; Muhammad Wildan Rizqi Miftahussanadi (Fakultas Kehutanan Universitas Mulawarman, 2021)
The Pecut kuda plant is one of the plants of the genus Stachytarpheta which is found in tropical regions, including Indonesia. In Indonesia this plant is found in East Kalimantan which grows wild. This study aims to determine the type of secondary metabolites and the level of toxicity of the leaves of horse whip (Stachytarpheta jamaicenesis (L.) Vahl). The research stages were sample drying, sample maceration, filtered, concentrated with a rotary evaporator, phytochemical and toxicity tests using linear regression values to determine the LC50 value with SAS probit analysis. Phytochemical test results showed that the pecut horse leaf extract in the n-hexane fraction contained flavonoids, quinones and steroids, the ethyl acetate fraction contained alkaloids, steroids, saponins, flavonoids and quinones and the methanol fraction contained phenolic flavonoids, quinones and saponins. The results of the toxicity test on Artemia salina L. shrimp larvae in the fraction of n-hexane, ethyl acetate and methanol obtained LC50 values of 0.036 ppm, 5.24 ppm and 29.51 ppm, respectively. Based on the LC50 value, it can be concluded that the three fractions are very toxic, but the most toxic is the n-hexane fraction (LC50 = 0.036 ppm).